Exploring Influences on Theory of Mind Impairment in Opioid Dependent Patients - Eidenmueller, Katharina; Grimm, Franz; Hermann, Derik; Frischknecht, Ulrich; Montag, Christiane; Dziobek, Isabel; Kiefer, Falk; Bekier, Nina Kim (Frontiers in Psychiatry, 2021)
Theory of mind (ToM) is an aspect of social cognition impaired in different addictive disorders, including opioid addiction. This study aimed at replicating ToM deficits in opioid dependent patients undergoing opioid maintenance treatment (OMT) and exploring the influence of substance use related variables, executive functions (EF) and childhood maltreatment on ToM in OMT patients. 66 OMT patients were tested using the Movie for Assessment of Social Cognition (MASC) and compared with the data of healthy controls. Furthermore, OMT patients underwent testing for executive functions and filled in the Childhood Trauma Questionnaire (CTQ). Performance on the MASC was significantly poorer in the OMT group than in the control group, even when recent additional drug use and psychiatric comorbidities were controlled for. No correlations were found between ToM and substance use related factors. Aspects of ToM performance in OMT patients correlated significantly with different EF domains. ToM correlated significantly with the CTQ scales for physical maltreatment. The results confirm impaired ToM in OMT patients and highlight EF and childhood maltreatment as influential factors. The lack of associations between ToM and substance use related variables and the association with childhood maltreatment suggest that ToM impairments might be a risk factor predating substance abuse.